HUBUNGAN STRATEGI COPING IBU DENGAN KUALITAS HIDUP ANAK THALASEMIA - Widya Fandri; Veny Elita; Safri Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Thalassemia is a chronic disease in children that causes the children to underwent hospitalization for at least one month in a year, and routine treatment for a long time. Physical and psychological change in children with thalassemia cause dependence children with family especially mothers and can affect the quality of life of children with thalassemia. The aim of this research is to assess the relationship between coping strategy of mother with quality of life of children with thalassemia. A descriptive design was conducted through cross-sectional correlation. The sampling technique was incidental sampling with consist of 30 respondents. The instrument of this study based on a standard questionnaire coping strategy (way of coping) and questionnaire pediatric quality of life inventory (PedsQL). The data were analyzed by using univariate about describes the characteristics of respondents and bivariate describes the relationship of two variables with fisher test. The results of this study indicate that approximately (76,2%) mothers using problem focused coping strategies have children with normal life quality and around (77,8%) of mothers using emotion focused coping strategies have children with quality of life at risk. The statistic result show that, there were relationship of coping strategy of Mother with quality of life of children thalasemia (p 0,013 <α 0,05). This study recommend to nurses in providing nursing care not only focus on treating thalassemia disease in children, but also can overcome the psychological impact of mother who become the main caregiver in the process of treatment and care of children with thalassemia, so that an optimal nursing care can be provided.Keywords: coping strategy, quality of life, thalassemia